Proximate composition, mineral elements content and physicochemical characteristics of Adansonia digitata L seed oil - IBRAHIM YAAGOUB ERWA; ALSHIFAA MOHAMMED ALI; ERAMA ALI KHALID; AWADALLA B. OMER; OMER ADAM OMER ISHAG (International Journal of Pharma and Bio Sciences, 2019)
Recently, the demand for seeds has increased as a source of oils. Adansonia digitata L (Malvaceae) seed oil has been utilized by some African communities as food, traditional medicine and cosmetic. This research was conducted to draw attention to the proximate composition, mineral elements content of baobab seeds and physicochemical properties of baobab seeds oil. Standard analytical methods were used to estimate the proximate and mineral element’s content of Adansonia digitata L. seeds and the seeds oil was evaluated for its physicochemical characteristics. Baobab seeds were found to be a good source of energy (374.23 ± 1.55 kcal/100 g), protein (21.20 ± 0.56%), and crude fat (21.23 ± 0.15%). The other proximate composition of the seeds were as follows; moisture (6.35 ± 0.05%), ash (3.27 ± 0.06%), crude fiber (23.37 ± 0.25%) and carbohydrate (24.32 ± 0.25%). The major mineral elements present in the seed involved magnesium (86.92 1.24 mg/100g), potassium (36.36 0.22 mg/100g), sodium (22.56 0.12 mg/100g), calcium (6.10 0.15 mg/100g) and iron (2.45 ± 0.02 mg/100 g). The physicochemical properties of extracted seed oil had the following values: oil content 21.23 ± 0.15 %, density 0.95 ± 0.007 g cm-3, kinematic viscosity 46.05 cSt, acid value 3.08 ± 0.25 mg KOH g-1, saponification value 95.37 ± 0.86 mg KOH g-1, peroxide value 6.60 ± 0.04 mEq kg-1 and iodine value 80.29 ± 0.07 mg g-1. Fatty acid profile of the oil revealed high unsaturated fatty acids contents (34.73% Elaidic acid and 28.95% 8, 11-Octadecadienoic acid), whereas palmitic was the major saturated acid (23.74%). Therefore our analytical results revealed that baobab seed is a good source of energy and nutrients for human nutrition.